Pengembangan Game Edukasi Genetic Match Berbasis Problem Based Learning dalam Meningkatkan Pemahaman Materi Pewarisan Sifat (Hukum I Mendel) - Cinta Salsabila Putri Harahap; Rasyidah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop the Problem Based Learning (PBL)-based Genetic Match educational game as a learning medium for the topic of trait inheritance, particularly Mendel's First Law, and to determine its feasibility, practicality, and effectiveness in improving students' conceptual understanding at MA Darul Azhariyyun Medan. This study employed a Research and Development (R&D) method using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 20 twelfth-grade students of MA Darul Azhariyyun Medan in the 2025/2026 academic  year.  The  data collection instruments consisted of material and media expert validation sheets, student response questionnaires, and conceptual understanding tests in the form of pretest and posttest. The data were analyzed using descriptive quantitative methods through feasibility percentages, student responses, and N-Gain scores. The validation results showed that the Genetic Match educational game was categorized as highly valid based on material and media expert assessments. Student responses indicated that the developed media was practical for use in learning. Furthermore, the effectiveness test results based on N-Gain scores showed an increase in students' conceptual understanding in the high category. Therefore, the PBL-based Genetic Match educational game was declared valid, practical, and effective as a Biology learning medium for the topic of trait inheritance, particularly Mendel's First Law. Keywords: Educational Game, Genetic Match, Problem Based Learning, Research and Development, Trait Inheritance